Pelatihan Produksi dan Strategi Pemasaran Kripik Ubi Jalar Di Kelurahan Pal Putih Kota Sorong - -, Susetyowati Sofia; Evi Mufrihah Zain; Digor Mufti; Latifah Dian Iriani; Ahmad Jamil; Muhammad Amin; Agilistya Rahayu (Universitas 45 Surabaya, 2022)
Sweet potato is one of the raw materials that is easy to get in West Papua, especially in the Pal Putih village which is located close to the market. The purpose of this training is that mothers or mothers in the Pal Putih village can have skills in processing Sweet Potatoes into Sweet Potato Chips that have good quality. This training not only increases knowledge of mothers in product manufacturing but is also able to implement marketing strategies by paying attention to product quality, packaging, packaging appearance aesthetics, branding and labeling; Housewives who take part in the training are encouraged or motivated to make sweet potato chips business so that they can increase their income. The implementation of activities is carried out with the following steps: Observation; Completion of service licensing and socialization; Training; Material reinforcement; and Discussion. The implementation of Community Service Activities is described as follows: Production training, marketing strategy, entrepreneurship motivation; Training on the initial preparation before producing, the production process, the packaging process, the labeling process.